Pemuliaan Angklung melalui Model Desa Binaan Berbasis Wisata Seni dan Budaya - Juju Masunah (LP2M ISBI Bandung, 2012)
Angklung has been awarded by UNESCO as one of the intangible world heritages from Indone- sia. One of the angklung preservation methods is through community based education. This article describes the result of research and community service activities to explore a model of community empowerment based on art and culture that uses Sundanese angklung instruments and local tradi- tional performing arts to attract tourism in Ciater Village, Subang. This research used a participato- ry action research method where researchers participate actively along with the community to create a touristic event involving art and culture. The findings of this research present that to empower a community using art and culture as an event for a tourist destination occurs by a collaborative work between local community, intelectuals, and bussiness. The community of Ciater village presented their innovation and creativity with Sundanese angklung music and local traditional performing arts in order to serve seventy tourists (artists) from Southeast Asia and Europe on October 7, 2011 for the first time.Â Keywords: Sundanese angklung, tourism of culture, Ciater Village.